1975
DOI: 10.1055/s-0028-1098531
|View full text |Cite
|
Sign up to set email alerts
|

Early Gastric Cancer — Experience in Germany

Abstract: The analysis of 87 cases of early gastric cancers does not demonstrate significant differences from findings which are reported in the Japanese literatur, above all as far as the macroscopic types, the histological pattern and the topographic distribution is concerned. The frequency of that diagnose during the fourth and fifth decade of the patients is hereby remarkable. The first biopsy allowed the diagnose of a carcinoma in the majority of all cases. The number of diagnosis of early gastric cancer increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Fibreoptic endoscopy has become widely accepted in European countries only within the past seven years and the use of double contrast radiology is not widespread outside Japan. Nonetheless, there are encouraging signs that 'early' gastric cancer is becoming more frequently recognised in centres outside Japan which are using improved diagnostic methods (Miller and Kauffmann, 1974;Elster et al, 1975;Fevre et al, 1976;Machado et al, 1976). Our own findings also suggest this possibility.…”
Section: Discussionsupporting
confidence: 52%
“…Fibreoptic endoscopy has become widely accepted in European countries only within the past seven years and the use of double contrast radiology is not widespread outside Japan. Nonetheless, there are encouraging signs that 'early' gastric cancer is becoming more frequently recognised in centres outside Japan which are using improved diagnostic methods (Miller and Kauffmann, 1974;Elster et al, 1975;Fevre et al, 1976;Machado et al, 1976). Our own findings also suggest this possibility.…”
Section: Discussionsupporting
confidence: 52%
“…It is, however, impossible countries. 8,16. to review a collectible number of such cases at one institution.…”
mentioning
confidence: 99%
“…Some authors have reported two histological types of EGC (4, 12); others, three types (3,8,13) and some four, histological types (17). Finally, others ( I 9) recognize five microscopical types of EGC.…”
mentioning
confidence: 99%